2015
DOI: 10.1039/c5ra00817d
|View full text |Cite
|
Sign up to set email alerts
|

Praseodymium oxide nanostructures: novel solvent-less preparation, characterization and investigation of their optical and photocatalytic properties

Abstract: Praseodymium oxide (Pr6O11) nanostructures were prepared via a new simple solvent-less route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(46 citation statements)
references
References 25 publications
1
44
0
1
Order By: Relevance
“…La(OH) 3 and La 2 O 3 have been studied extensively as support materials for luminescent activator ions, such as Tb(III) and Eu(III) ions [3,[27][28][29][30]. Other lanthanides oxides have also extensively been studied [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 98%
“…La(OH) 3 and La 2 O 3 have been studied extensively as support materials for luminescent activator ions, such as Tb(III) and Eu(III) ions [3,[27][28][29][30]. Other lanthanides oxides have also extensively been studied [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 98%
“…The development of a reliable and simple way for preparation of nanostructured Nd 2 O 3 is of great importance to the potential 30 investigation of its characteristics. It has been reported that particle size and shape have key impact on the characteristics of nanoscale materials 19,20 . So, exploring desirable and appropriate ways to produce nanostructured Nd 2 O 3 and controlling its morphology and particle size seems necessary and noteworthy.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption peak appear at 3426 cm -1 in Fig. 1b is attributable to the v(OH) stretching vibration of physisorbed water molecules [22]. The characteristic band of the barium stannate appears at 646 cm -1 [26] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…So far, reverse micelle, solid state, coprecipitation, combustion and solgel approach [11][12][13][14][15] have been reported to synthesize barium stannate. Since shape, size and size distribution have key and considerable impact on the characteristics and applications of the nanomaterials, several procedures have been reporting on particle size and shape controlled preparation of nanomaterials [16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%